Effects of short-term in-season break detraining on repeated-sprint ability and intermittent endurance according to initial performance of soccer player. - Alejandro Rodríguez-Fernández; Javier Sánchez-Sánchez; Rodrigo Ramirez-Campillo; José Antonio Rodríguez-Marroyo; José Gerardo Villa Vicente; Fabio Yuzo Nakamura (PLoS ONE, 2018)
To better understand the detraining effects in soccer, the purpose of the study was to analyse if performance level of soccer players modulate repeated-sprint ability (RSA) and intermittent endurance changes during 2-weeks of detraining (i.e., in-season break). Seventeen professional and sixteen young elite soccer players of two different teams performed, before and after 2-weeks of detraining, the RSA test and the Yo-Yo Intermittent Recovery Test, level 1 (YYIR1). Before detraining, professional players perform better (p < 0.05) RSA best time (RSAbest) than young players. A decrease (p < 0.05) in RSAbest, RSA total time (RSAtotal) and mean time (RSAmean) performance was observed in both teams, without changes in RSA fatigue index (Sdec). No significant changes in distance covered during YYIR1 was observed in any team. Before detraining, faster players from both teams (FG) (following the median split technique, soccer players with RSAbest ≤ 3.95 s) performed better (p < 0.01) in RSAtotal, RSAmean and RSAbest, but worse (p < 0.01) in Sdec. Although FG and the slower players (SG, RSAbest > 3.95 s) showed a worse (p < 0.05) RSAtotal, RSAbest and RSAmean performance after detraining (ES = 1.5, 1.4 and 2.9; ES = 0.6, 1.2 and 0.6; for FG and SG, respectively), the deterioration was greater in the FG for RSAbest (p < 0.05) and RSAtotal (ES = 1.46). After detraining, FG improved (p < 0.05) Sdec performance. In conclusion, a 2-week in-season break (detraining) period induced a worse RSA, with no effect on intermittent endurance in professional and elite young soccer players, with greater detrimental effects on RSAtotal and RSAbest in FG. In addition, Sdec does not seem to be sensitive to changes in RSA after a 2-week in-season break.